SIFAT FISIK DAN MEKANIK KAYU GERUNGGANG (CRATOXYLON ARBORESCEN Bl) YANG DIDENSIFIKASI BERDASARKAN WAKTU PENGUKUSAN DAN WAKTU KEMPA - Megawati, .; Usman, Fadillah H.; Tavita, Gusti Eva (JURNAL HUTAN LESTARI, 2016)
The increasing demand for wood every years is not balanced with the availability of raw materials in nature, especially high-quality wood. Hence the need for an effort to partially overcome this condition by using low quality wood (III-IV) such as Gerunggang wood (Cratoxylon arborescen Bl). Samples were made of Gerunggang wood with size of 30 cm x 8 cm  x 4 cm with a target of 30% reduction in thickness. Physical and mechanical properties testing refers to the British Standard Methods 373 (1957). Parameters measured were color and touch impression, water content, density, dimensional changes, MOE, MOR and MCS). This research used  factorial experiment in a random design complete with  2 factors. Factor A steaming time (50 minutes, 60 minutes and 70 minutes) and factor B pressing time (40 minutes, 60 minutes and 80 minutes) each made 3 times repeats. The results showed Gerunggang wood was densification by steaming and pressing time produce physical and mechanical properties better. The best treatment in this research were at the steaming time treatment 60 minutes and 80 minutes pressing time. Keywords :  Cratoxylon arborescen Bl, densification, physical and mechanical.